2009
DOI: 10.1007/s11882-009-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

New concepts of hive formation in cholinergic urticaria

Abstract: Patients with cholinergic urticaria (CU) show a number of small, short-lasting hives when their body core temperature increases, usually during sweating following exercise or bathing. The precise mechanism(s) of hive formation in CU has been unclear except for the involvement of acetylcholine. We recently reported that most CU patients show immediate-type skin responses to their own sweat, whereas the rest of CU patients have positive autologous serum skin tests (ASSTs). The former group produced satellite whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 46 publications
(59 reference statements)
1
39
0
2
Order By: Relevance
“…Consequently, excess acetylcholine stimulates sensory nerve terminals to produce pain and acts on the muscarinic CHRM3 on mast cells in the vicinity of sweat glands to cause weals. In accord with this hypothesis, an intradermal test with cholinergic agents was typically positive in this type of CU 1 . However, we experienced a case of CU patients with AGH which showed the absence of CHRM3 expression even on mast cells, 11 suggesting that some molecules other than acetylcholine may involve the development of CU.…”
Section: Cholinergic Urticaria Associated With Acquired Generalized Hsupporting
confidence: 53%
See 1 more Smart Citation
“…Consequently, excess acetylcholine stimulates sensory nerve terminals to produce pain and acts on the muscarinic CHRM3 on mast cells in the vicinity of sweat glands to cause weals. In accord with this hypothesis, an intradermal test with cholinergic agents was typically positive in this type of CU 1 . However, we experienced a case of CU patients with AGH which showed the absence of CHRM3 expression even on mast cells, 11 suggesting that some molecules other than acetylcholine may involve the development of CU.…”
Section: Cholinergic Urticaria Associated With Acquired Generalized Hsupporting
confidence: 53%
“…The sweat glands receive sympathetic innervations but express muscarinic acetylcholine receptors, which are normally expressed on parasympathetic nervous systems; therefore, acetylcholine is considered to be a central signal mediator for the secretion of sweat. Previous reports have demonstrated that subcutaneous injection of cholinergic agents induce sweating and the development of numerous pin‐point hives in patients with CU, and that the symptoms of CU are inhibited by prior atropinization of the skin 1 . In addition, recent studies have shown that not only sweat glands but also mast cells express muscarinic cholinergic receptor 3 (CHRM3), which is a responsible cholinergic receptor for sweating 2 .…”
Section: The Essential Role Of Acetylcholine In the Development Of Chmentioning
confidence: 99%
“…It is known that follicular and non-follicular forms have different pathogenic mechanisms8. It is hypothesized that hypersensitivity to autologous serum and sweat may be involved in the wheal formation of the former and the latter type, respectively8.…”
Section: Discussionmentioning
confidence: 99%
“…Although the symptoms of FDEIA and cholinergic urticaria occur after exercise, FDEIA is clearly distinguishable fi'om cholinergic urticaria, which appears as pinpoint-sized wheals with surrounding erythema that occur after sweating (5,6). Patients with FDEIA usually have immunoglobulin E (IgE) antibodies and positive skin prick tests (SPTs) against the causative food allergens.…”
mentioning
confidence: 99%